Dermatologic neoplasms: a perspective from Makurdi, North Central Nigeria - Ajetunmobi, Olanrewaju I.; Dzuachii, Donatus O. (International Journal of Research in Dermatology, 2017)
Background: Skin cancers are the commonest malignancies in Caucasians but are relatively less common in dark skinned persons. They are strongly linked to ultraviolet exposure, skin melanin content, and immune status. Methods: This study reviewed all histologically diagnosed skin neoplasms at the Federal Medical Centre, Makurdi from January 2012 to December 2016. Results: A total of 84 neoplasms were seen, with 42 (50%) being malignant. Of the malignant lesions, Squamous cell carcinomas were the most frequent (45.2%), followed by melanomas (23.8%). The lower limb was the most frequent site of both benign and malignant neoplasms, while a male to female ratio of 0.88:1 was observed. Conclusions: A relatively high UV radiation intensity, combined with a predominance of outdoor agricultural based activities, alongside chronic ulcerative/inflammatory lesions and a high HIV burden all indicate a need for widespread enlightenment and screening campaigns to prevent occurrence of skin cancers and aid early diagnosis.